2019
DOI: 10.1139/cjpp-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase is a source of oxidative stress in obese patients with chronic inflammation

Abstract: Obesity is an important preventable risk factor for morbidity and mortality from cardiometabolic disease. Oxidative stress (including in visceral adipose tissue) and chronic low-grade inflammation are the major underlying pathomechanisms. Monoamine oxidase (MAO) has recently emerged as an important source of cardiovascular oxidative stress. The present study was conducted to evaluate the role of MAO as contributor to reactive oxygen species (ROS) production in white adipose tissue and vessels harvested from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Due to the fact that serotonin metabolism disorder is one of the pathogens in panic, the results of the present study are confirmed. In other words, increased serotonin levels elevate its catabolism and as a result the activity of the enzyme monoamine oxidase, which in turn leads to the induction and increase of oxidative stress (Hamzekolaei et al, 2020; Sturza, et al, 2019; Sturza, et al, 2019; Xu et al, 2019), demonstrated in our results by reduced level of glutathione and glutathione peroxidase activists and elevated levels of carbonyl proteins. Our previous study also reported an increase in malondialdehyde levels as an indicator of oxidative stress (Hamzekolaei et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Due to the fact that serotonin metabolism disorder is one of the pathogens in panic, the results of the present study are confirmed. In other words, increased serotonin levels elevate its catabolism and as a result the activity of the enzyme monoamine oxidase, which in turn leads to the induction and increase of oxidative stress (Hamzekolaei et al, 2020; Sturza, et al, 2019; Sturza, et al, 2019; Xu et al, 2019), demonstrated in our results by reduced level of glutathione and glutathione peroxidase activists and elevated levels of carbonyl proteins. Our previous study also reported an increase in malondialdehyde levels as an indicator of oxidative stress (Hamzekolaei et al, 2020).…”
Section: Discussionsupporting
confidence: 56%
“…Selective serotonin reuptake inhibitors, used in the treatment of panic patients, elevate serotonin level and catabolism (Quagliato et al., 2019). Various studies have shown that increased monoamine oxidase activity induces oxidative stress, which causes inflammation and cardiovascular disease (Gupta et al., 2019; Sturza, et al, 2019; Sturza, et al, 2019; Xu et al, 2019). Since serotonin metabolism abnormalities and increased monoamine oxidase activity have been reported in panic patients, the aim of present study was to evaluate homocysteine levels as a biomarker of heart disease in panic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, STAT3 has also been indicated as one of the crucial targets for treating IBDs, although activation of STAT3 is likely to occur in both innate and acquired cell types [29]. MAOA, as a monoamine oxidase, though is not directly associated with IBDs, is highly related with inducing oxidative stress in obese people who are suffering chronic in ammation [42]. Recently, dysregulation of MAOA has also been linked to speci c microbe alteration [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have demonstrated that MAO plays an important role in cardiovascular oxidative stress (e.g., ROS) and induction of inflammation by promoting endothelial dysfunction [ 32 , 33 ]. In addition, MAO-A expression, activity, and function are altered in IL-13-induced monocytes and in A549 lung carcinoma cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%